Long-term persistence of HCV resistance-associated substitutions after DAA treatment failure - Dietz, Julia; Müllhaupt, Beat; Buggisch, Peter; Graf, Christiana; Peiffer, Kai-Henrik; Matschenz, Katrin; Schattenberg, Jörn M.; Antoni, Christoph Helmer; Mauss, Stefan; Niederau, Claus; Discher, Thomas; Trauth, Janina; et al. (Journal of hepatology, 2023)
Background & Aims - Data on the long-term persistence of HCV resistance-associated substitutions (RASs) after treatment with direct-acting antivirals (DAAs) are limited. This study evaluated the persistence of NS3, NS5A, and NS5B RASs for up to 5 years after the end of treatment (EOT). - Methods - We included samples from 678 individuals with an HCV genotype (GT) 1 or 3 infection and virologic DAA treatment failure collected in the European Resistance Database. NS3, NS5A, and NS5B were sequenced, and clinical parameters were evaluated. - Results - A total of 242 individuals with HCV GT1a (36%), 237 with GT1b (35%), and 199 (29%) with GT3 and a DAA failure were included. After protease inhibitor failure, the frequencies of NS3 RASs were 40-90% after the EOT. NS3 RASs disappeared rapidly in GT1b and GT3 after follow-up month 3 but were stable (≥60%) in GT1a owing to Q80K. The SOF-resistant NS5B RAS S282T was only found in individuals with GT3a. Non-nucleoside NS5B RASs were frequent in GT1 (56-80%) and decreased to 30% in GT1a but persisted in GT1b. NS5A RASs were very common in all GTs after NS5A inhibitor failure (88-95%), and even after follow-up month 24, their frequency was 65% and higher. However, RASs in GT1b had a stable course, whereas RASs in GT1a and GT3 declined slightly after follow-up month 24 (GT1a, 68%; GT1b, 95%; and GT3, 65%), mainly because of the slow decline of high-level resistant Y93H. - Conclusions - We found that low-to medium-level RASs persisted, whereas high-level resistant RASs disappeared over time. Different patterns of RAS persistence according to HCV subtype could have implications for retreatment with first-generation DAAs and for global HCV elimination goals. - Impact and implications - There are little data on the long-term persistence of HCV resistance-associated substitutions (RASs) after DAA treatment failure, and RASs could have an impact on the efficacy of a rescue treatment. Especially in countries with limited availability of VOX/VEL/SOF or G/P/SOF, different patterns of RAS persistence could have implications for retreatment with first-generation DAAs and for global HCV elimination goals. The different patterns of RAS persistence identified in this study can be used to derive general rules regarding the persistence of RASs after DAA failure that could be applied by physicians in less developed countries to plan individualized HCV retreatment.
Online verfügbar: 27. August 2022, Artikelversion: 15. Dezember 2022
Mitglieder der German HCV Resistance Study Group, University Hospitals, Academic Hospitals, Local study sites (private practices), Germany: J. Balavoine, E. Giostra, M. Berning, J. Hampe, A. Canbay, W. Steckstor, W. Schmiegel, N.H. Brockmeyer, A. De Gottardi, A. Rauch, N. Semmo, J. Fischer, M. Gress, H. Heinzow, G. Hilgard, H. Schmidt, A. Herrmann, A. Stallmach, D. Hoffmann, U. Protzer, H. Klinker, P. Schulze, A. Kodal, A. Kremer, J. Siebler, M. Löbermann, T. Götze, J. Weigt, A. Lohse, J. Von Felden, S. Jordan, C.M. Lange, R. Zachoval, J. Mayerle, A. Maieron, D. Moradpour, J.-P. Chave, C. Moreno, M. Muche, H.-J. Epple, M. Müller-Schilling, F. Kocheise, B. Müllhaupt, K. Port, K. Deterding, H. Wedemeyer, M. Cornberg, M. Manns, L. Reinhardt, V. Ellenrieder, J. Rissland, D. Semela, U. Spengler, J. Rockstroh, E. Roeb, M. Sprinzl, P. Galle, R. Stauber, W. Stremmel, B. Strey, R. Thimme, T. Boettler, F. Tacke, A. Teufel, R. Vogelmann, M. Ebert, K. Tomasiewicz, C. Trautwein, T. Koenen, T. Weber, P. Wietzke-Braun, R. Günther, E. Zizer, J. Backhus, T. Seufferlein, W. Angeli, S. Beckebaum, C. Doberauer, E. Durmashkina, A. Hackelsberger, A. Erhardt, A. Garrido-Lüneburg, H. Gattringer, D. Genné, M. Gschwantler, F. Gundling, S. Hametner, R. Schöfl, C. Hartmann, T. Heyer, C. Hirschi, A. Jussios, S. Kanzler, N. Kordecki, M. Kraus, U. Kullig, S. Wollschläger, L. Magenta, B. Terziroli Beretta-Piccoli, M. Menges, L. Mohr, K. Muehlenberg, C. Niederau, B. Paulweber, A. Petrides, M. Pinkernell, R. Piso, W. Rambach, M. Reiser, B. Riecken, A. Rieke, J. Roth, M. Schelling, P. Schlee, A. Schneider, D. Scholz, E. Schott, M. Schuchmann, U. Schulten-Baumer, A. Seelhoff, A. Stich, F. Stickel, J. Ungemach, E. Walter, A. Weber, T. Winzer, W. Abels, M. Adler, F. Audebert, C. Baermann, E. Bästlein, R. Barth, K. Barthel, W. Becker, J. Behrends, J. Benninger, F. Berger, D. Berzow, T. Beyer, M. Bierbaum, O. Blaukat, A. Bodtländer, G. Böhm, N. Börner, U. Bohr, B. Bokemeyer, H.R. Bruch, D. Bucholz, O. Burkhard, N. Busch, C. Chirca, R. Delker, J. Diedrich, M. Frank, M. Diehl, A. Dienethal, P. Dietel, N. Dikopoulos, M. Dreck, F. Dreher, L. Drude, K. Ende, U. Ehrle, K. Baumgartl, F. Emke, R. Glosemeyer, G. Felten, D. Hüppe, J. Fischer, U. Fischer, D. Frederking, B. Frick, G. Friese, B. Gantke, P. Geyer, H.R. Schwind, M. Glas, T. Glaunsinger, F. Goebel, U. Göbel, B. Görlitz, R. Graf, H. Gruber, G. Härter, M. Herder, T. Heuchel, S. Heuer, K.-H. Höffl, H. Hörster, J.-U. Sonne, W. P. Hofmann, F. Holst, M. Hunstiger, A. Hurst, E. Jägel-Guedes, C. John, M. Jung, B. Kallinowski, B. Kapzan, W. Kerzel, P. Khaykin, M. Klarhof, U. Klüppelberg, Wolfratshausen, K. Klugewitz, B. Knapp, U. Knevels, T. Kochsiek, A. Körfer, A. Köster, M. Kuhn, A. Langekamp, B. Künzig, R. Link, M. Littman, H. Löhr, T. Lutz, G. Knecht, U. Lutz, D. Mainz, I. Mahle, P. Maurer, C. Mayer, V. Meister, H. Möller, R. Heyne, D. Moritzen, M. Mroß, M. Mundlos, U. Naumann, O. Nehls, K. R. Ningel, A. Oelmann, H. Olejnik, K. Gadow, E. Pascher, J. Petersen, A. Philipp, M. Pichler, F. Polzien, R. Raddant, M. Riedel, S. Rietzler, M. Rössle, W. Rufle, A. Rump, C. Schewe, C. Hoffmann, D. Schleehauf, W. Schmidt, G. Schmidt-Heinevetter, J. Schmidtler-von Fabris, L. Schneider, A. Schober, S. Niehaus-Hahn, J. Schwenzer, B. Seegers, T. Seidel, G. Seitel, C. Sick, K. Simon, D. Stähler, F. Stenschke, H. Steffens, K. Stein, M. Steinmüller, T. Sternfeld, B. Strey, K. Svensson, W. Tacke, G. Teuber, K. Teubner, J. Thieringer, A. Tomesch, U. Trappe, J. Ullrich, G. Urban, S. Usadel, A. Von Lucadou, F. Weinberger, M. Werheid-Dobers, P. Werner, T. Winter, E. Zehnter, A. Zipf
Gesehen am 09.09.2024